A process device and method for solving the problem of acid carrying at the outlet of sulfuric acid absorption tower
By combining regular packing and saddle bulk packing in the sulfur acid-making absorption tower and laying bulk packing in the acid mist capture layer, the problems of uneven gas and liquid distribution and acid-carrying in the traditional absorption tower are solved, and the absorption efficiency and equipment stability are improved.
Patent Information
- Application Number
- CN202411925735.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-01
AI Technical Summary
After the scale of the traditional sulfur acid-making absorption tower is expanded and the process is improved, the gas-liquid distribution is uneven and the contact is poor, resulting in a decrease in absorption efficiency and an increase in energy consumption. At the same time, the acid problem of the absorption tower exit is serious, affecting the stability and production efficiency of the equipment.
The device includes a cylinder demister, a tube acid divider and a filler layer. The regular filler in the filler layer is used in combination with the saddle bulk filler. The regular filler is prepared by materials such as zirconium titanate and borate. The bulk filler is laid in the acid mist capture layer to improve the gas-liquid contact and acid mist capture efficiency.
Through the improved filler structure and device design, the absorption efficiency is significantly improved, the acid mist content at the absorption tower outlet is reduced, the equipment service life is extended, and energy consumption and system pressure drop are reduced.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of chemical production, and in particular to a process device and method for solving the problem of acid carrying at the outlet of a sulfuric acid absorption tower. Background Art
[0002] In the sulfuric acid production process, the absorption tower is one of the core equipment, and its operating efficiency and stability are directly related to the production quality and cost of sulfuric acid. In the traditional flue gas absorption process, the selection and distribution of fillers inside the absorption tower, the uniform contact between the gas and liquid phases, and the effective management of heat are the key factors affecting the absorption efficiency. However, with the expansion of production scale and the improvement of process requirements, traditional absorption towers and their supporting acid distributor systems have gradually exposed many shortcomings. In particular, when regular fillers are used to improve mass transfer efficiency, although the gas-liquid distribution is optimized to a certain extent, as the tower diameter increases, the problems of uneven gas-liquid distribution and poor contact become more and more significant, which is the so-called "amplification effect", which directly leads to a decrease in absorption efficiency and an increase in energy consumption. The strong exothermic phenomenon accompanying the sulfuric acid production process will not only cause energy waste, but may also pose a threat to the stable operation of the system if this part of the heat cannot be effectively managed and utilized.
[0003] As a key link in the sulfuric acid production process, if the outlet flue gas pipeline of the first absorption tower contains acid, it will not only corrode the pipeline and damage the safety of the production environment, but also have a serious impact on subsequent equipment such as cold and hot heat exchangers, causing corrosion, perforation, and leakage of the tube bundle, thereby reducing the overall conversion rate and affecting the efficiency and stability of the entire production line. In addition, the acid problem will also affect the downstream four-stage catalyst, causing powdering and scarring, sharply increasing system resistance, increasing the load of the acid production device, and even causing the device to shut down in severe cases. Although traditional leak detection and plugging methods can temporarily alleviate the problem, the heat exchange area of the cold exchange tube bundle is reduced after multiple plugging, which destroys the thermal balance and affects the stability of the catalyst inlet temperature, resulting in a decrease in the overall conversion rate and excessive acid mist. Summary of the invention
[0004] In order to solve the problems mentioned in the above background technology, the present invention provides a process device and method for solving the problem of acid carrying at the outlet of sulfuric acid absorption tower.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] A device for solving the problem of acid at the outlet of a sulfuric acid absorption tower comprises an absorption tower, wherein the absorption tower comprises a cylindrical demister, a tubular acid distributor and a packing layer, wherein a cake-shaped wire mesh demister is fixedly installed inside the cylindrical demister, and acid mist capturing layers are arranged above and below the tubular acid distributor, wherein rectangular saddle-shaped bulk fillers with a thickness of 400-450 mm and a height of 38 mm are laid inside the acid mist capturing layer.
[0007] According to another aspect of the present invention, a process for solving the problem of acid at the outlet of a sulfuric acid absorption tower is provided, using the above-mentioned device, comprising the following steps: introducing the raw gas into the absorption tower through the bottom feed port, and passing the raw gas through the top discharge port after being treated by the packing layer, the tubular acid distributor, and the cylindrical demister to enter the subsequent process;
[0008] Among them, the packing layer includes structured packing and bulk packing. The bulk packing is evenly laid on the structured packing to ensure that the two layers of packing are in close contact with each other without gaps. The volume ratio of the structured packing to the bulk packing is 3:1, that is, the structured packing accounts for 3 / 4 of the total volume and the bulk packing accounts for 1 / 4 of the total volume.
[0009] Further, the structured packing comprises the following steps:
[0010] Place zirconium titanate and borate in a ball mill, add water and PEG-2000, and ball mill for 12-24 hours. Set the speed to 300-400 rpm to ensure that the raw materials are evenly mixed. Dry in an oven at 100°C to constant weight, pass through a 200-mesh sieve, and then add polyaluminum ferrosilicate to obtain a structured filler.
[0011] Furthermore, the mass ratio of zirconium titanate, borate, water, PEG-2000 and polyaluminium ferrosilicate is (6-10):(1-3):(10-20):(0.3-0.4):(20-25), and the borate includes one of boracite, hydroborite, borax and colemanite.
[0012] Further, the polyaluminium ferrosilicate is prepared by the following steps:
[0013] S1. Add fly ash into 20-30% hydrochloric acid solution, react at 65-75°C for 2-3h, and filter and separate after the reaction to obtain a solid phase and an iron-aluminum salt solution;
[0014] S2, mixing the iron aluminum salt solution with 30-40% sodium hydroxide solution, adjusting the pH value to 3, reacting at 60° C. for 2-3 hours, and maintaining the stirring speed at 100-200 rpm to obtain an iron aluminum hydroxide sol;
[0015] S3, adding the solid phase to a 10-20% sodium hydroxide solution, stirring evenly to obtain a silicate solution, and then acidifying with a 20-30% dilute sulfuric acid solution in two steps, first adjusting the pH value to 4, reacting for 30-60 minutes, and then adjusting the pH value to 2, reacting for 1-2 hours, to obtain a polysilicate sol;
[0016] S4. Mix the polysilicate sol and the aluminum iron hydroxide sol, and stir at room temperature at a speed of 100-200 rpm for 2-3 hours. The stirring speed is . After the reaction is completed, let it stand for 24 hours to obtain polyaluminum iron silicate.
[0017] Furthermore, in step S1, the mass ratio of fly ash to hydrochloric acid solution is 1:(0.04-0.08), the mass ratio of solid phase to sodium hydroxide solution in step S3 is 1:(0.1-0.5), and the mass ratio of polysilicate sol to iron aluminum hydroxide sol in step S4 is (1.2-1.4):1.
[0018] Furthermore, the bulk filler is a rectangular saddle-shaped bulk ceramic filler with a height of 76 mm.
[0019] Beneficial effects of the present invention:
[0020] 1. In the technical solution of the present invention, by laying a rectangular saddle-shaped bulk filler of a specific thickness and height in the acid mist capture layer and combining it with a structured filler, the uniform contact between the gas and liquid phases in the absorption tower is ensured, the gas-liquid contact area is increased, and the effective capture of the acid mist is promoted, thereby significantly improving the absorption efficiency. The volume ratio of the structured filler to the bulk filler is designed to be 3:1, which not only ensures the close contact of the filler layer, but also makes full use of the advantages of the two fillers to achieve efficient absorption of the gas.
[0021] 2. In the technical solution of the present invention, structured fillers such as zirconium titanate and borate are used as structured fillers, which are combined with boehmite through a specific preparation process to form a structured filler with excellent physical and chemical properties, improve the specific surface area, pore volume and adsorption performance of the filler, and optimize the average pore size, so that it can capture target molecules more efficiently. The modification and uniform dispersion of the structured filler promote the formation of a specific morphology and structure of boehmite, further enhance the ability to interact with gas or liquid molecules, and improve the adsorption capacity and rate. As a part of the structured filler, the preparation process of polyaluminum ferrosilicate makes full use of fly ash, an industrial waste, to achieve effective utilization of resources and sustainable development of the environment. The polyaluminum ferrosilicate prepared by acidification, alkalization and other steps can play a synergistic role in the preparation process of the structured filler, improve the dispersibility, stability and anti-agglomeration performance of the filler, and further enhance the filler's ability to absorb gas.
[0022] 3. In the technical solution of the present invention, by partially replacing the bulk fillers in the absorption tower with modified or upgraded high-efficiency fillers, the workload of technical transformation is minimized, the acid mist content in the flue gas at the outlet of the absorption tower is effectively reduced, and the corrosion of condensed acid on the cold and hot heat exchanger is significantly reduced, thereby extending the service life of the equipment. In addition, this solution also reduces the amount of acid mist entering the fourth stage of the converter, reduces the contact frequency between the acid mist and the catalyst, and effectively protects the activity of the catalyst. At the same time, by optimizing the filler structure, the liquid holding capacity of the demister is also reduced, thereby reducing the total pressure drop of the absorption tower and the electricity cost of the main fan. DETAILED DESCRIPTION
[0023] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Unless otherwise specified, the raw materials used in the present invention are all conventional products purchased from the market.
[0025] Preparation Example 1
[0026] Polyaluminium ferrosilicate comprises the following steps to prepare:
[0027] S1. Add 10 kg of fly ash into 0.4 kg of 20% hydrochloric acid solution, react at 65°C for 2 hours, and filter and separate after the reaction to obtain a solid phase and an iron-aluminum salt solution;
[0028] S2, mixing the iron aluminum salt solution with a 30% sodium hydroxide solution, adjusting the pH value to 3, reacting at 60° C. for 2 h, and maintaining the stirring speed at 100 rpm to obtain an iron aluminum hydroxide sol;
[0029] S3, adding 10 kg of the solid phase to 1 kg of 10% sodium hydroxide solution, stirring evenly to obtain a silicate solution, and then acidifying with a 20% dilute sulfuric acid solution in two steps, first adjusting the pH value to 4, reacting for 30 minutes, and then adjusting the pH value to 2, reacting for 1 hour, to obtain a polysilicic acid sol;
[0030] S4. Mix 12 kg of polysilicate sol and 10 kg of aluminum iron hydroxide sol, and stir at room temperature at a speed of 100 rpm for 2 hours. The stirring speed is . After the reaction is completed, let it stand for 24 hours to obtain polyaluminum iron silicate.
[0031] Preparation Example 2
[0032] Polyaluminium ferrosilicate comprises the following steps to prepare:
[0033] S1. Add 10 kg of fly ash into 0.6 kg of 25% hydrochloric acid solution, and react at 70°C for 2.5 hours. After the reaction is completed, filter and separate to obtain a solid phase and an iron-aluminum salt solution;
[0034] S2, mixing the iron aluminum salt solution with a 35% sodium hydroxide solution, adjusting the pH value to 3, reacting at 60° C. for 2.5 h, and maintaining the stirring speed at 150 rpm to obtain an iron aluminum hydroxide sol;
[0035] S3, adding 10kg of the solid phase to 3kg of 15% sodium hydroxide solution, stirring evenly to obtain a silicate solution, and then acidifying with 25% dilute sulfuric acid solution in two steps, first adjusting the pH value to 4, reacting for 45min, and then adjusting the pH value to 2, reacting for 1.5h, to obtain a polysilicate sol;
[0036] S4. Mix 13 kg of polysilicate sol and 10 kg of ferric aluminum hydroxide sol, and stir at room temperature at a speed of 150 rpm for 2.5 hours. The stirring speed is . After the reaction is completed, let it stand for 24 hours to obtain polyaluminum iron silicate.
[0037] Preparation Example 3
[0038] Polyaluminium ferrosilicate comprises the following steps to prepare:
[0039] S1. Add 10 kg of fly ash into 0.8 kg of 30% hydrochloric acid solution, and react at 75°C for 3 hours. After the reaction is completed, filter and separate to obtain a solid phase and an iron-aluminum salt solution;
[0040] S2, mixing the iron aluminum salt solution with 40% sodium hydroxide solution, adjusting the pH value to 3, reacting at 60° C. for 3 h, and maintaining the stirring speed at 200 rpm to obtain an iron aluminum hydroxide sol;
[0041] S3, adding 10kg of the solid phase to 5kg of 20% sodium hydroxide solution, stirring evenly to obtain a silicate solution, and then acidifying with 30% dilute sulfuric acid solution in two steps, first adjusting the pH value to 4, reacting for 60min, and then adjusting the pH value to 2, reacting for 2h, to obtain a polysilicate sol;
[0042] S4. Mix 14 kg of polysilicate sol and 10 kg of aluminum iron hydroxide sol, and stir at room temperature at a speed of 200 rpm for 3 hours. The stirring speed is . After the reaction is completed, let it stand for 24 hours to obtain polyaluminum iron silicate.
[0043] Preparation Example 4
[0044] The structured packing is prepared by the following steps:
[0045] Put 6kg of zirconium titanate and 1kg of boracic acid into a ball mill, add 10kg of water and 0.3kg of PEG-2000, and ball mill for 12h. The speed is set to 300rpm to ensure that the raw materials are evenly mixed. Dry in an oven at 100°C to constant weight, pass through a 200-mesh sieve, and add 20kg of polyaluminum ferrosilicate obtained in Preparation Example 1 to obtain a structured filler.
[0046] Preparation Example 5
[0047] The structured packing is prepared by the following steps:
[0048] Put 8kg of zirconium titanate and 2kg of hydroborite into a ball mill, add 15kg of water and 0.35kg of PEG-2000, and ball mill for 18h. The speed is set to 350rpm to ensure that the raw materials are evenly mixed. Dry in an oven at 100°C to constant weight, pass through a 200-mesh sieve, and add 22kg of polyaluminum ferrosilicate obtained in Preparation Example 2 to obtain a structured filler.
[0049] Preparation Example 6
[0050] The structured packing is prepared by the following steps:
[0051] Put 10kg of zirconium titanate and 3kg of borax into a ball mill, add 20kg of water and 0.4kg of PEG-2000, and ball mill for 24 hours. The speed is set to 400rpm to ensure that the raw materials are evenly mixed. Dry in an oven at 100°C to constant weight, pass through a 200-mesh sieve, and add 25kg of polyaluminum ferrosilicate obtained in Preparation Example 3 to obtain a structured filler.
[0052] Example 1
[0053] In a sulfuric acid plant with an annual output of 600,000 tons of sulfuric acid, the outlet of the first absorption tower carries 30 kg of acid per hour at 100% load.
[0054] A process method for solving the problem of acid contamination at the outlet of a sulfuric acid absorption tower, comprising the following steps: introducing raw gas into the absorption tower through a bottom feed port, and passing the raw gas through a packing layer, a tubular acid distributor, and a cylindrical demister, and then passing the raw gas into a top discharge port to enter a subsequent process, wherein no acid contamination occurs at the discharge port of the primary absorption tower, and no acid contamination occurs when the device load is increased to 100%;
[0055] The packing layer is provided with the structured packing prepared in Preparation Example 4 and the rectangular saddle-shaped bulk ceramic packing with a height of 76 mm, the rectangular saddle-shaped bulk ceramic packing with a height of 76 mm is laid on the structured packing, and the volume ratio of the structured packing to the bulk packing is 3:1;
[0056] A cake-shaped wire mesh demister is fixedly installed inside the cylindrical demister, and an acid mist capturing layer is arranged above and below the tubular acid distributor. A rectangular saddle-shaped bulk filler with a thickness of 400 mm and a height of 38 mm is laid in the acid mist capturing layer.
[0057] Example 2
[0058] In a sulfuric acid plant with an annual output of 600,000 tons of sulfuric acid, the outlet of the first absorption tower carries 30 kg of acid per hour at 100% load.
[0059] A process method for solving the problem of acid contamination at the outlet of a sulfuric acid absorption tower, comprising the following steps: introducing raw gas into the absorption tower through a bottom feed port, and passing the raw gas through a packing layer, a tubular acid distributor, and a cylindrical demister, and then passing the raw gas into a top discharge port to enter a subsequent process, wherein no acid contamination occurs at the discharge port of the primary absorption tower, and no acid contamination occurs when the device load is increased to 100%;
[0060] The packing layer is provided with the structured packing prepared in Preparation Example 5 and the rectangular saddle-shaped bulk ceramic packing with a height of 76 mm, the rectangular saddle-shaped bulk ceramic packing with a height of 76 mm is laid on the structured packing, and the volume ratio of the structured packing to the bulk packing is 3:1;
[0061] A cake-shaped wire mesh demister is fixedly installed inside the cylindrical demister, and acid mist capturing layers are arranged above and below the tubular acid distributor. Rectangular saddle-shaped bulk filler with a thickness of 430 mm and a height of 38 mm is laid in the acid mist capturing layer.
[0062] Example 3
[0063] In a sulfuric acid plant with an annual output of 600,000 tons of sulfuric acid, the outlet of the first absorption tower carries 30 kg of acid per hour at 100% load.
[0064] A process method for solving the problem of acid contamination at the outlet of a sulfuric acid absorption tower, comprising the following steps: introducing raw gas into the absorption tower through a bottom feed port, and passing the raw gas through a packing layer, a tubular acid distributor, and a cylindrical demister, and then passing the raw gas into a top discharge port to enter a subsequent process, wherein no acid contamination occurs at the discharge port of the primary absorption tower, and no acid contamination occurs when the device load is increased to 100%;
[0065] The packing layer is provided with the structured packing prepared in Preparation Example 6 and the rectangular saddle-shaped bulk ceramic packing with a height of 76 mm, the rectangular saddle-shaped bulk ceramic packing with a height of 76 mm is laid on the structured packing, and the volume ratio of the structured packing to the bulk packing is 3:1;
[0066] A cake-shaped wire mesh demister is fixedly installed inside the cylindrical demister, and acid mist capturing layers are arranged above and below the tubular acid distributor. Rectangular saddle-shaped bulk fillers with a thickness of 450 mm and a height of 38 mm are laid in the acid mist capturing layer.
[0067] Comparative Example 1
[0068] The difference between this comparative example and Example 1 is that polyaluminium ferrosilicate is used instead of the structured packing prepared in Preparation Example 4, and the remaining steps are the same as in Example 1. It is measured that the outlet of an absorption tower carries 6 kg of acid per hour under 100% load.
[0069] Comparative Example 2
[0070] The difference between this comparative example and Example 2 is that zirconium titanate is used instead of the structured packing prepared in Preparation Example 5, and the remaining steps are the same as in Example 2. It is measured that the outlet of an absorption tower carries 27 kg of acid per hour under 100% load.
[0071] Comparative Example 3
[0072] The difference between this comparative example and Example 3 is that borax is used instead of the structured packing prepared in Preparation Example 6, and the remaining steps are the same as in Example 3. It is measured that the outlet of an absorption tower carries 12 kg of acid per hour under 100% load.
[0073] Embodiment 1-3 all used the structured packing obtained by different preparation examples, and combined with the rectangular saddle type bulk ceramic packing. In these embodiments, the first-stage absorption tower discharge port did not appear the acid phenomenon under 100% load. The volume ratio of structured packing to bulk packing was 3:1, and the bulk packing was laid above the structured packing, which may optimize the air flow distribution, improve the absorption efficiency, and effectively prevent the acid mist from being taken out. The acid mist capture layer arranged up and down in the tubular acid distributor further captures the acid mist that may escape, and strengthens the acid removal effect.
[0074] Comparative Example 1 uses polyaluminium ferrosilicate to replace the structured packing of Preparation Example 1. The results show that the outlet of an absorption tower still carries 6kg of acid per hour at 100% load. This shows that the acid removal effect of using only polyaluminium ferrosilicate without making it into a structured packing is not as good as the combination of structured packing and bulk packing. Comparative Example 2 uses zirconium titanate to replace the structured packing of Preparation Example 2. The results show that the acid carrying amount is as high as 27kg / h. Zirconium titanate itself may not have sufficient ability to adsorb and capture acid mist, so the effect is not good. Comparative Example 3 uses borax to replace the structured packing of Preparation Example 3. The results show that the acid carrying amount is 12kg / h. Although borax may have certain adsorption properties, its effect is still far inferior to the combination of structured packing and bulk packing.
[0075] Due to the orderliness of its structure, structured packing can more effectively distribute the airflow and increase the gas-liquid contact area, thereby improving the absorption efficiency. At the same time, the microporous structure on its surface may help capture and adsorb acid mist. Bulk packing can further disperse the airflow and increase the gas-liquid contact time, thereby enhancing the absorption effect. Its irregular shape and surface structure also help capture and fix acid mist. The acid mist capture layer above and below the tubular acid distributor can capture the escaped acid mist and prevent it from entering the subsequent process.
[0076] In summary, the combination of structured packing and bulk packing used in Examples 1-3, and the design of the acid mist capture layer above and below the tubular acid separator, together constitute an efficient acid removal system, which can effectively solve the problem of acid carryover at the outlet of the sulfuric acid absorption tower.
[0077] In the description of the specification, the description with reference to the terms "embodiment", "various embodiments" and the like means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or preparation example are included in at least one embodiment or preparation example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or preparation example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or preparation examples in a suitable manner.
[0078] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A device for solving the problem of acid at the outlet of sulfuric acid absorption tower, characterized in that: The absorption tower comprises a cylindrical demister, a tubular acid distributor and a packing layer. A cake-shaped wire mesh demister is fixedly installed inside the cylindrical demister. Acid mist capturing layers are arranged above and below the tubular acid distributor. Rectangular saddle-shaped bulk packing with a thickness of 400-450 mm and a height of 38 mm is laid in the acid mist capturing layer.
2. A process for solving the problem of acid at the outlet of sulfuric acid absorption tower, using the device described in claim 1, characterized in that: The method comprises the following steps: introducing the raw gas into the absorption tower through the bottom feed port, and after being processed by the packing layer, the tubular acid separator, and the cylindrical demister, passing the raw gas into the top discharge port to enter the subsequent process; The packing layer includes structured packing and bulk packing, the bulk packing is evenly laid on the structured packing, and the volume ratio of the structured packing to the bulk packing is 3:
1.
3. A process for solving the problem of acid at the outlet of sulfuric acid absorption tower according to claim 2, characterized in that: The structured packing is prepared by the following steps: Place zirconium titanate and borate in a ball mill, add water and PEG-2000, and ball mill for 12-24 hours. Set the speed to 300-400 rpm to ensure that the raw materials are evenly mixed. Dry in an oven at 100°C to constant weight, pass through a 200-mesh sieve, and then add polyaluminum ferrosilicate to obtain a structured filler.
4. A process for solving the problem of acid at the outlet of sulfuric acid absorption tower according to claim 3, characterized in that: The mass ratio of zirconium titanate, borate, water, PEG-2000 and polyaluminium ferrosilicate is (6-10):(1-3):(10-20):(0.3-0.4):(20-25), and the borate includes one of boracite, hydroborite, borax and colemanite.
5. A process for solving the problem of acid at the outlet of sulfuric acid absorption tower according to claim 3, characterized in that: Polyaluminium ferrosilicate comprises the following steps to prepare: S1. Add fly ash into 20-30% hydrochloric acid solution, react at 65-75°C for 2-3h, and filter and separate after the reaction to obtain a solid phase and an iron-aluminum salt solution; S2, mixing the iron aluminum salt solution with 30-40% sodium hydroxide solution, adjusting the pH value to 3, reacting at 60° C. for 2-3 hours, and maintaining the stirring speed at 100-200 rpm to obtain an iron aluminum hydroxide sol; S3, adding the solid phase to a 10-20% sodium hydroxide solution, stirring evenly to obtain a silicate solution, and then acidifying with a 20-30% dilute sulfuric acid solution in two steps, first adjusting the pH value to 4, reacting for 30-60 minutes, and then adjusting the pH value to 2, reacting for 1-2 hours, to obtain a polysilicate sol; S4. Mix the polysilicate sol and the aluminum iron hydroxide sol, and stir at room temperature at a speed of 100-200 rpm for 2-3 hours. The stirring speed is . After the reaction is completed, let it stand for 24 hours to obtain polyaluminum iron silicate.
6. A process for solving the problem of acid at the outlet of sulfuric acid absorption tower according to claim 5, characterized in that: The mass ratio of fly ash to hydrochloric acid solution in step S1 is 1:(0.04-0.08), the mass ratio of solid phase to sodium hydroxide solution in step S3 is 1:(0.1-0.5), and the mass ratio of polysilicate sol to iron aluminum hydroxide sol in step S4 is (1.2-1.4):
1.
7. A process for solving the problem of acid in the outlet of sulfuric acid absorption tower according to claim 2, characterized in that: The bulk filler is a rectangular saddle-shaped bulk ceramic filler with a height of 76 mm.